The Mediterranean Basin and Southern Europe in a warmer world: what can we learn from the past? - Guiot, Joël; Kaniewski, David (Frontiers in Earth Science, 2015)
Since the late-nineteenth century, surface temperatures have non-uniformly increased worldwide. The repercussion of the global warming in drylands, such as in the Mediterranean, may become a main source of concern in a near future, as it is often accompanied by increased droughts, that will severely degrade water supply and quality. History shows that access to water resources has always presented a challenge for societies around the Mediterranean throughout the Holocene (roughly the last 10,000 years). Repeatedly, adverse climate shifts seem to have interacted with social, economic and political variables, exacerbating vulnerabilities in drier regions. We present a reconstruction of the Holocene climate in the Mediterranean Basin using an innovative method based on pollen data and vegetation modeling. The method consists in calculating the inputs of the vegetation model so that the outputs fit the pollen data, using a Bayesian framework. This model inversion is particularly suited to deal with increasing dissimilarities between past millennia and the last century, especially due to a direct effect of CO2 on vegetation. The comparison of fardistant past and last century shows that the intensity of century-scale precipitation fall, amplified by higher temperatures and then evapotranspiration, appears to be unmatched over the last 10,000 years and the comparison between west and east precipitation anomalies show a clear see-saw effect through all the Holocene, in particular during the dry episodes of Near and Middle East. As a consequence that Tthe recent climatic change seems thento have been unprecedented during the last 10,000 years in the Mediterranean Basin,.over the next few decades, Mediterranean societies will likely be more critically vulnerable to climate change, than at any dry period of the past. We show also that adverse climate shifts are often correlated with the decline or collapse of Mediterranean civiliszations, particularly in the eastern Basin.